A Modified Surgical Technique for Endoscopic Carpal Tunnel Release - Jing Xu, M.D., Ph.D.; Xiaotian Jia, M.D., Ph.D.; Yinglu Zhao, M.D., Ph.D.; Jianyun Yang, M.D., Ph.D. (Arthroscopy Techniques)
Carpal tunnel syndrome has a high incidence rate in the population. The focus of this Technical Note is on how to release the nerve efficiently, safely and easily. We use a technique for endoscopic carpal tunnel release. This article details the surgical technique for performing the whole transverse carpal ligament transection arthroscopically.